Дослідження ринку соняшникової олії у світі та Україні - Шандрівська, О. Є.; Питуляк, Н. С.; Греб, О. І.; Shandrivska, O. Ye.; Pytulyak, N. S.; Hreb, O. I. (Видавництво Львівської політехніки, 2024)
Представлено результати комплексного аналізу ринку соняшникової олії у світі та українського ринку соняшникової олії в частині його взаємодії з суміжними ринками. Дослідження спрямоване на визначення основних тенденцій, чинників впливу та пер- спектив розвитку цього стратегічного сегменту сільськогосподарського сектору. Проведено оцінювання концентрації ринку соняшникової олії в Україні в секторі підприємств-продуцентів соняшникової олії за допомогою індексу концентрації, індексу Лінда, індексу Херфіндаля-Хіршмана, індексу Джинні.

The purpose of the study is to identify the results of the study of the Ukrainian oil market in terms of assessing the concentration of the sunflower oil market, taking into account the world experience of the oil market and its related sector – the sunflower market. The following research methods were used: empirical, synthesis, induction method (for a comprehensive study of the sunflower oil market and the related oilseeds market), statis- tical methods (to identify the dynamics of the oil market and the oilseeds market in the world and Ukraine); analysis (to study the dynamics of changes in vegetable oil production, including by country, as well as by type of oilseeds in the world); index method (to assess the concentration of the oil market in Ukraine) and other research methods. The results of the study of the sunflower oil market at the global and Ukrainian levels confirm that the production and consumption of this product determine stable demand, given its importance in the world-class food industry. As a leading sunflower oil producer, Ukraine plays a key role in the global market, providing large export volumes. Despite the positive dynamics of the sunflower oil market, major challenges have been identified, such as global price fluctuations, climate change and competition from other vegetable oils. For the further development of the Ukrainian sunflower oil market, it is important to continue to introduce innovative approaches, improve product quality and ensure sustainable production. The results of this study are of interest to participants in the sunflower oil and sunflower market, who seek to implement various types of marketing concepts for the active development of thesemarkets. In order to obtain the desired results, sunflower oilmarket producerswill be interested in studying supply and demand, assessing trade prospects, sales volumes, exports and imports, which in turn will allow them to work efficiently in the market and meet the needs of all sunflower oil market participants. The value of this study lies in its contribution to understanding the dynamics and characteristics of the sunflower oil market at the global andUkrainian levels. In particular, it thoroughly analyses production and consumption trends, highlighting the key factors that determine the stable demand for this product in the food industry. The paper highlights the unique aspects of Ukraine's contribution to the global sunflower oil market, the specifics of export activities, and the impact of external factors on the market situation among producers.
Sunflower oil market research in the world and Ukraineh
Keywords: ринок соняшнику; ринок соняшникової олії; посівні площі; види рослинних олій; гострота конкуренції; індекс концентрації. індекс Лінда; індекс Херфін- даля-Хіршмана; індекс Джинні; sunflower market; sunflower oil market; sown areas; types of vegetable oils; competition intensity; concentration index; Linda index; Herfindahl-Hirschman index; Ginni index; 339.564; 633